Benefits of increased cover crop diversity for predators and biological pest control depend on the landscape context. Issue 3 (13th July 2021) - Beaumelle, Léa; Auriol, Arthur; Grasset, Marie; Pavy, Alice; Thiéry, Denis; Rusch, Adrien
Abstract: Increasing plant diversity in agricultural systems is a promising way to balance food production and biodiversity conservation. Biological pest control, a crucial ecosystem service delivered by natural enemies, could particularly benefit from increased plant diversity at the local scale. Such positive effects however often depend on the landscape context that shapes the pool of natural enemy species available and their ability to colonize newly created habitats. However, how the landscape context modulates the local effect of plant diversity on natural enemies and pest control services remains unclear. Here, we manipulated the diversity of cover crops (2 versus 20 plant species) in nine pairs of vineyards located along a landscape gradient ranging from 20 to 60% of semi‐natural habitats. We sampled natural enemy communities in the soil and foliage and measured the predation rate of an important moth pest in European vineyards ( Lobesia botrana ). Diverse cover crops enhanced the abundance of natural enemies by 140% across the experiment, but without changing their taxonomic richness and composition. We further found a distance‐decay effect of cover crops on natural enemy abundance across cover crop types. The landscape context remarkably modulated the effects of local plant diversity on natural enemy abundance and predation rates. While predation rates were on average similar in the low and high cover crop diversity treatments across the experiment, diverse cover crops had higher positive effects on predation and natural enemies in simple (<50% semi‐natural habitats) than complex landscapes. Predation rates increased from 11 to 42% in the high compared with low cover crop diversity treatments in simple landscapes. Synthesis and applications : Our study demonstrates the benefits of increasing plant diversity at the local scale to enhance the abundance of natural enemies as well as the level of biological pest control services in vineyard agroecosystems. Diverse cover crops mostly benefit natural enemies and biological pest control in simplified landscapes, highlighting that the success of local agroecological practices in improving biodiversity and ecosystem services depends on the landscape context. Thus, we suggest that a strategic spatial arrangement of agricultural practices increasing local plant diversity is necessary to maximize beneficial effects on biodiversity and ecosystem services. Abstract : Increasing the diversity of cover crops in vineyards enhanced the abundance of natural enemies by 140% overall. Predation rates of an important moth pest also increased, particularly in simple landscapes (from 20 to 50% of semi‐natural habitats in a 1 km radius around each field). Abstrait: Augmenter la diversité des couverts végétaux dans les systèmes agricoles représente une manière prometteuse de concilier production agricole et conservation de la biodiversité. La régulation biologique des ravageurs, un service écosystémique clé rendu par les ennemis naturels, pourrait tout particulièrement bénéficier de l'augmentation de la diversité végétale au niveau local. Cependant, de tels effets positifs pourraient dépendre du contexte paysager, car celui‐ci détermine le pool d'ennemis naturels disponible et leur capacité à coloniser les nouveaux habitats créés par l'établissement de couverts végétaux diversifiés. La manière dont le paysage module l'effet local de la diversité végétale sur les ennemis naturels et le service de régulation biologique reste pourtant mal connue. Dans cette étude, nous avons manipulé la diversité du couvert végétal (2 versus 20 espèces de plantes) à l'intérieur des parcelles de 9 paires de vignes situées le long d'un gradient paysager allant de 20 à 60% d'habitats semi‐naturels. Nous avons échantillonné les ennemis naturels du sol et du feuillage de la vigne, et mesuré les taux de prédation d'un papillon ravageur important dans les vignobles européens ( Lobesia botrana ). Les résultats indiquent que les couverts végétaux plus diversifiés augmentent l'abondance des ennemis naturels de 140% en moyenne, mais sans changer la richesse taxonomique et la composition des communautés d'ennemis naturels. Dans les deux traitements, l'abondance des ennemis naturels diminuait à mesure que l'on s'éloignait des couverts végétaux semés. Notre étude montre que le contexte paysager détermine l'effet des couverts végétaux diversifiés sur l'abondance des ennemis naturels et les taux de prédation. Si les taux de prédation étaient en moyenne similaires dans les couverts végétaux peu et fortement diversifiés à travers les paysages, les couverts plus diversifiés avaient des effets positifs plus importants sur la prédation et les ennemis naturels dans les paysages simplifiés (< 50% d'habitats semi‐naturels) que dans des paysages complexes. Dans ces paysages simplifiés, les taux de prédation ont augmenté de 11 à 42% dans les couverts végétaux diversifiés par rapport aux couverts peu diversifiés. Synthèse et application : Cette étude montre qu'augmenter la diversité locale des plantes permet d'accroître l'abondance des ennemis naturels et le service de régulation des ravageurs dans les vignobles, tout particulièrement dans des contextes paysagers simplifiés, avec de faibles proportions d'habitats naturels. Cela souligne que l'efficacité des pratiques agro‐écologiques locales à accroître la biodiversité et les services écosystémiques dépend du contexte paysager. Un arrangement spatial stratégique des pratiques agro‐écologiques qui s'appuient sur l'augmentation de la diversité végétale est donc nécessaire pour maximiser ses effets bénéfiques sur la biodiversité et les services écosystémiques.